2011
DOI: 10.1002/sia.3406
|View full text |Cite
|
Sign up to set email alerts
|

ToF‐SIMS characterization of the lipid layer on the hair surface. II : Effect of the 18‐MEA lipid layer on surface hydrophobicity

Abstract: In this study, the effect of the damage level of 18-MEA on the hydrophobicity of hair surfaces and the mechanism of technology for replenishment of the lipid on damaged hair surfaces were examined using Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS). The surface amount of 18-MEA was measured in Japanese women by ToF-SIMS. It was obvious that the 18-MEA was decreased drastically by coloring treatments, especially in individuals who underwent such treatments more than two times per year. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Consequently, it was confirmed that the surface cuticles of the subjects elder than 40 are prone to be broken and this phenomenon is promoted by aging . It has been variously reported that reduction of 18‐MEA badly affects hair and that chemical treatments, such as bleaching, cause its drastic loss . In this study, it was revealed that aging also causes loss of 18‐MEA, especially in the age range elder than 40.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Consequently, it was confirmed that the surface cuticles of the subjects elder than 40 are prone to be broken and this phenomenon is promoted by aging . It has been variously reported that reduction of 18‐MEA badly affects hair and that chemical treatments, such as bleaching, cause its drastic loss . In this study, it was revealed that aging also causes loss of 18‐MEA, especially in the age range elder than 40.…”
Section: Discussionmentioning
confidence: 67%
“…To maintain a hair surface healthy, it is known that the fatty acid 18‐MEA plays an important role. This lipid is covalently bound to the cuticle surface and provides lubrication, smooth alignment and contributes to the fine luster of hair fibers …”
Section: Discussionmentioning
confidence: 99%
“…The 18‐MEA existing on the hair surface is detected as the negative molecular ion peak at m / z 341, the molecular ion peak of 18‐MEA . The oxidative cleavage of thioester bonds was evaluated by monitoring the change in the peak m / z 341 intensity . Figure shows the dependence of the decrease of the peaks at m / z 341 and m / z 76.…”
Section: Resultsmentioning
confidence: 99%
“…The surface damage of hair leads to changes in the physical properties such as increase in hydrophilicity and friction, which decreases hair quality. In previous studies it was revealed that serious damage leading to cleavage of disulfide bonds in cystine and decreasing of the fatty acids occur on the hair surface as shown in Fig. .…”
Section: Introductionmentioning
confidence: 99%
“…3-nm layer called the epicuticle. The chemical composition of the top layer has been determined in detail by various analytical techniques [18,19]. The epicuticle normally has a hydrophobic surface due to the extensive coverage by 18-methyl eicosanoic acid (18-MEA) (ca.…”
Section: Introductionmentioning
confidence: 99%